Tecer saberes sens??veis: educa????o humanizadora e a constru????o da narrativa hist??rica - Sousa, Renata Fl??via de Oliveira (2018)
History is responsible for inserting man into his context, into his environment and into time. It is able to reconnect us in our complexity and make us perceive as practicing and responsible subjects for the creations of the world, an indispensable issue for human formation and survival in a time marked by gratuitous violence and fragility of ties. This analysis aims at: the construction of historical narrative as a practice of complex thought for a humanizing education. It seeks to analyze approximations and distances between history and literature, focusing on the construction of the narrative sensitive, relating to ideas of the complex thought of Edgar Morin. It understands that the uses existing in this relation can help in the development of a sensitive and humanizing education, thus contributing to an education that exercises complex thought. For this I use as reference the cultural history and the thinking of Edgar Morin to think a sensitive historical writing, inspired by literature and that is able to access our complexity. The research fits in a theoretical discussion using bibliographical sources, from academic works, magazines, theoretical books bases and literary books that come to contribute to the creation of the writing and discussions. In its methodology, we tried to construct a sensitive narrative using literature as instrument, as is the proposal launched in the research objectives.It was noticed that historical writing using the inputs provided by the literature as a key to access the human in its various parts (demens and sapiens, poetic and prosaic, etc.) is able to open doors to the practice of complexity. This narrative constructed with possibilities of rich interpretation stimulating the "ecological" thinking is able to make see the other and to perceive the constructed history, inserting the human in the nucleus of knowledge and responsibility in the historical construction, besides putting its parts, prosaic and poetic in a dance with this language full of windows. The results of this research indicate a path to the practice of complex thought in education and scientific production, because when we produce a sensitive writing that allows us to know and include the subject in the making of the world, we can also bring more than information, bring teachings to life.